The effect of the alternative solutions to formaldehyde and xylene on tissue processing - Ilgin Aydin; Kutsal Yörükoglu; Sultan Cingöz; Sinem Agilkaya (Wolters Kluwer Medknow Publications, 2013)
Introduction and Aim: To assess the impact of new alternative solutions to formaldehyde and xylene on tissue processing, 13 different tissue processings were designed and performed on thirteen different tissues by using five different fixatives (formaldehyde, Glyo-Fixx® , FineFix® , Cell-block® , Green-Fix® ) and four different clearing agents (xylene, Sub-X® , Bio-clear® , Shandon Xylene Substitute® ). Materials and Methods: Hematoxylin and Eosine stained sections were compared by using qualitative histomorphological criterions. Histochemical and immunohistochemical (IHC) staining results were compared with qualitative and quantitative data obtained by a computer program, respectively. Tissue sections were tested for the availability of chromogenic in situ hybridization, deoxyribonucleic acid (DNA) and ribonucleic acid (RNA) extraction, and DNA quality by polymerase chain reaction. Results: The quality of sections was well for all tissue processings. All alternative solutions were suitable for histochemistry. IHC staining results showed that alternative solutions that contain glyoxal as active agent need optimization for this application. The clearance of signals with chromogenic in situ hybridization were nearly same and well for all tissue samples. Furthermore, tissue processes that do not contain formaldehyde were found to be superior on preservation of nucleic acids. Conclusion: Formaldehyde-free fixatives and alternative clearing agents have potential in routine pathology and research to replace formaldehyde and xylene.